THE INFLUENCE OF PEDAGOGICAL COMPETENCE AND TEACHER SELF-EFFICACY ON INCLUSIVE EDUCATION SERVICES - ROHLIAH, Siti (Journal of Education and Leadership in Education, 2025)
The purpose of this study is to examine the direct effects of: (1) teachers’ pedagogical competence on inclusive education services, (2) teachers’ self-efficacy on inclusive education services, and (3) pedagogical competence on teachers’ self-efficacy at the elementary school level in Tangerang City. This research used a causal survey method with path analysis. The population consisted of 183 inclusive school teachers in Jati uwung and Periuk Districts, with a sample of 126 selected through proportional random sampling. The results show that: (1) pedagogical competence has a positive and significant effect on inclusive education services (t = 8.378 > 1.979, path coefficient = 0.407, correlation = 0.601, p = 0.000), with a weak relationship; (2) teacher self-efficacy has a positive and significant effect on inclusive education services (t = 7.962 > 1.979, path coefficient = 0.366, correlation = 0.582, p = 0.000), with a very strong relationship; and (3) pedagogical competence has a positive and significant effect on teacher self-efficacy (t = 6.962 > 1.979, path coefficient = 0.530, p = 0.000), with a moderate relationship.